KAJIAN YURIDIS PERSEKONGKOLAN TENDER PENGADAAN PEKERJAAN KONSTRUKSI PEMBANGUNAN STADION MANDALA KRIDA DAERAH ISTIMEWA YOGYAKARTA - Eksy Puji Rahayu; Sudiyana Sudiyana (Kajian Hasil Penelitian Hukum, 2022)
Abstract Tender conspiracy is the most serious violation in business competition cases and is contrary to economic democracy, because it does not provide equal opportunities for every citizen to participate in the process of producing and marketing goods/services in a healthy, effective, and efficient business climate. In the KPPU's Decision Number 10/KPPU-I/2017 it is stated that, Reported Parties I to Reported Parties IX have been legally and convincingly proven to have conspired to tender in the procurement of construction work for the construction of the Mandala Krida Stadium. At the appeal level, the Sleman District Court handed down Decision Number 19/Pdt.Sus-KPPU/2019/PN Smn which rejected the Petitioners' objection. At the cassation level, the Supreme Court in Decision Number 893 K/Pdt.Sus-KPPU/2020 upheld Decision Number 19/Pdt.Sus-KPPU/2019/PN Smn and Decision Number 10/KPPU-I/2017. The purpose of this study is to find out, examine, and analyze the suitability of KPPU's handling of the case of conspiracy to tender the procurement of construction work for the construction of the Mandala Krida Stadium in the Province of Yogyakarta with the applicable laws and regulations, as well as those that are considered by judges both at the district court and the Supreme Court. in strengthening the KPPU's decision Number 10/KPPU-I/2017. This type of research includes normative legal research, using qualitative descriptive analysis. The results of the study show that the KPPU's handling of case Number 10/KPPU-I/2017 and the judges' considerations at the Sleman District Court and the Supreme Court have been in accordance with what is stipulated in the applicable legal provisions. However, the rule of reason approach used by KPPU in this case is considered inappropriate.